OUTBOND TRAINING SEBAGAI MEDIA ALTERNATIF PENINGKATAN KUALITAS KERJA TIM PTK-PNF - Widya Ayu Puspita; Prihaningsih Prihaningsih (JIV-Jurnal Ilmiah Visi, 2007)
Of the opinion that the quality of human resource determines the achievement of the organizational goals, this article introduces a number of training, one of which is out-bond training. This kind of training is discussed and related to its application in non-formal education. It can be developed for teamwork programs such as team building and team development, leadership programs, and personal programs. As out-bond training is based on experiential learning, quantum learning, participatory approach and observation and processing, it is considered appropriate for adult learning and outdoor activities and can be developed for non-formal education personnel. To complete this article, a general design of out-bond training is explained to be developed to meet the needs of non-formal education.